Arrythmic storm in patients with and without a myocardial infarction. (14th October 2021) - Garcia-Arribas, D; Fernandez Ramos, A; Viana, A; Rosillo, S; Caro-Codon, J; Armada, E; Carrion, I; Ferrera, C; Noriega, F.J; Lopez De Sa, E
Abstract: Introduction: Available data on arrhythmic storm (AS) is frequently obtained from retrospective observational series of patients who carry an implantable cardioverter defibrillator or who undergo ablation, and typically, patients with ST-elevation myocardial infarction (STEMI) as the cause of the AS are excluded. Therefore, this selection bias limits the evidence regarding mortality and prognosis of patients with AS due to STEMI. Purpose: Describe and compare the epidemiological and clinical characteristics, treatment, and outcomes of patients admitted for AS in the Acute Coronary Care Unit due to STEMI and other causes. Methods: Between 2006 and 2020, 187 episodes of AS in 165 patients were identified in two third level hospitals. There were 40 patients with STEMI and 147 patients with other causes of AS. Clinical characteristics, treatment and outcome were analysed. Results: Baseline characteristics are depicted in Figure 1. Risk profile of patients without STEMI was worse (they were older, had more often hypertension, and thyroid disturbances, and had worse NYHA class). Patients with STEMI were more frequently smokers. Ejection fraction was higher among STEMI patients. Predisposing features for AS (apart from myocardial ischemia) were also different. Ion disturbances were more common among STEMI patients (37.4% vs 67.5%, p=0.001). Heart failure or cardiogenic shock (27.9% vs 40.0%, p=0.140), infection (12.2% vs 7.5%, p=0.399) and bradycardia with acquired long QT syndrome (10.2% vs 10.0%, p=0.695) were similar in both groups. There were two episodes of myocarditis in patients without STEMI. The predominant arrythmia was also different. Ventricular fibrillation was more common in STEMI patients (4.8% vs 72.5%) while monomorphic ventricular tachycardia was more frequent patients without STEMI (80.3% vs 7.5%, p<0.001). STEMI patients had worse levels of pH (7.40 vs 7.25, p<0.001) and lactate (2.25mmol/L vs 5.56mmol/L, p>0.001) and required inotropics and vasopressors more frequently due to haemodynamic instability (15.0% vs 77.5%, p<0.001), mechanical support with intra-aortic balloon pump (5.4 vs 57.5%, p<0.001), ECMO (2.0% vs 7.5%, p=0.082), and other mechanical assist devices (0 vs 10.0%, p<0.001), and oral intubation (23.8% vs 90.0%, p<0.001). Pharmacologic treatment is described in Figure 2. Obviously, STEMI patients required more often percutaneous coronary intervention (8.2% vs 87.5%, p<0.001) and less frequently ventricular ablation (50.3% vs 0, p<0.001). Therapeutic hypothermia was more commonly used in STEMI patients due to out of hospital cardiac arrest (2.0% vs 52.5%, p<0.001). In-hospital mortality was higher in STEMI patients (11.6% vs 42.5%, p<0.001). Conclusion: Despite a worse cardiovascular profile in patients without STEMI, AS is associated with a worse haemodynamic situation and mortality in STEMI patients. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Beca para la Formaciόn e Investigaciόn en Cuidados Críticos Cardiolόgicos concedida por la Asociaciόn de Cardiopatía Isquémica y Cuidados Críticos Cardiolόgicosde la SEC